Pengaruh Kemandirian Belajar Terhadap Kemampuan Berfikir Kritis Diintervening Motivasi Belajar E-learning Ekonomi - Farliana, Nina; Setiaji, Khasan; Muktiningsih, Serdiyah (Universitas Negeri Makassar, 2021)
The aims of this study to determine the direct and indirect effect of independent learning on critical thinking skills with learning motivation as an intervening variable. This research is a quantitative research with a survey approach. This type of research is ex-post facto, with the sampling process using simple random sampling. The method of analysis used the normality test, linearity test, multicolonierity test, heteroscedasticity test, T test, path analysis, and descriptive analysis. The results showed that independent learning has a positive and significant direvt effect on learning motivation by 78,3 %. Learning motivation has a positive and significant direct effect on critical thinking skills by 61%. Learning independence has a positive and significant effect directly on the ability to think critically by 28,9%. Learning independence has a positive and significant indirect effect on critical thinking skills with learning motivation as an intervening variable of 47,8%. This shows that the good independent learning of students and good motivation to learn, it is able to improve the critical thinking skills of good students.